Aluminum phthalocyanine nanoparticles activation for local fluorescence spectroscopy in dentistry - J. O. Zolotareva; D. S. Farrakhova; E. N. Kupriyanova; V. B. Loschenov (Biomedical Photonics)
Early diagnosis of caries and tooth enamel microcracks is of great importance for preventing the destruction of healthy tooth enamel. Inorder to detect microcracks in the enamel and pathogenic microflora foci that can cause caries, nanoform of aluminum phthalocyanine (AlPc) can be used as a marker. In a colloidal solution, the nanoparticles do not fluoresce, unlike their molecular form. To convert the particle into its molecular form, it is necessary to have a solvent or specific environment (bacteria, macrophages, etc.). That is why the hydrophobic nanoparticles of aluminum phthalocyanine (nAlPc) can act as markers for detecting hidden pathogenic microflora during fluorescent diagnostics. Further reduction of the diagnosis time and increase the efficiency can be achieved by using biologically compatible surfactants as additional activators of nAlPc.In order to carry out local fluorescence spectroscopy of enamel microcracks and pathogenic microflora foci on the enamel surface, a model compound containing surfactants, auxiliary components and nAlPc colloid at a concentration of 10 mg/l was prepared.Studies on the interaction of the model compound with nAlPc and Protelan MST-35 with tooth enamel ex vivo have shown this surfactant to be a promising auxiliary activator of the nanoparticles, allowing conducting local fluorescence spectroscopy of the tooth enamel surface 3 min after application. In addition, statistical processing of the results showed the effectiveness of using the model compound for local fluorescence spectroscopy of the enamel surface in order to detect the enamel microcracks and the pathogenic microflora accumulation foci that can lead to the development of a cariogenic process.